Numerical Analysis of Lateral and Vertical Deformation of the Embedded Length of Monopile in a Sandy Soil - Noori, Fatema S.; Al-Qaisee, Ghusoon S.; Mohsin, Zainab M. (Civil Engineering Journal, 2026)
A monopile is a large-diameter steel cylinder partially inserted into seabeds; thus, it is one of the major selections of offshore wind and tower foundations. This study aimed to investigate the effect of monopile diameter, thickness, and ratio of soil embedded depth to height of water on the lateral and vertical displacements of the embedded part of the pile. In the study, the monopile was subjected to a lateral displacement equivalent to 10% of the pile diameter at the pile head in order to examine the lateral and vertical deformations of the embedded length of the pile. The three-dimensional finite element software PLAXIS 3D was used to simulate the study. The soil layer used consisted of one layer of medium-dense sandy soil. The study involved investigating the location along the embedded depths that exhibit zero lateral and vertical displacements; that location was found to depend on the monopile diameter, wall thickness, and ratio of embedded depth to water height. The depth of zero lateral displacement was found to increase as pile rigidity and wall thickness increase. The study shows that increasing the L/H ratio on the embedded depth of zero lateral displacement, LHzero, diminishes with increasing monopile diameter for the same wall thickness. Also, the variation of lateral displacement along pile length demonstrates a constant trend behavior regardless of pile thicknesses and diameters, but the depth of zero lateral displacement, LHzero, was varied. Furthermore, the monopile diameter effect on the vertical displacement shows that as the monopile diameter increases, the depth of zero vertical displacement decreases. Also, as L/H decreased, the depth of zero vertical displacement declined.